Web-Based Cooperation Information System at The Science Techno Park Technology Business Development Center - Jefril Rahmadoni; Ricky Akbar; Ullya Mega Wahyuni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Science Techno Park (STP) Unand's partnership with various government, business, and legal institutions will continue for the foreseeable future in order to disseminate innovators' knowledge to the larger community. The issue that frequently arises is that the file search procedure is tough to locate. Furthermore, the enormous number of inventors at Andalas University are recorded in Microsoft Excel files, making it difficult for users to locate inventory data. The data that is then entered is frequently duplicated, leaving the user perplexed about the information presented. As a result, at STP Unand's Technology Business Development Center, a web-based cooperative information system was created. The goal is for STP Unand's engagement with partners to be automated, and for data collecting on the number of inventors in Unand to be structured. The SDLC (Software Development Life Cycle) method is used in this study. SDLC is a software development cycle that encompasses software development techniques, phases, and tools. The waterfall paradigm was used in the design of this application. the waterfall method was successfully used to build or design a collaborative information system application. Based on the outcomes of each stage of the waterfall method, namely analysis, design, coding, and system testing, it is possible to conclude that the design of this collaborative information system application has been successfully built in accordance with needs.